2006
DOI: 10.3748/wjg.v12.i2.317
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-11 and Interleukin-11 receptor α in human colorectal adenocarcinoma; Immunohistochemical analyses and correlation with clinicopathological factors

Abstract: IL-11 and IL-11Ra are highly expressed in human colorectal adenocarcinoma and the IL-11Ra expression is correlated with clinicopathological factors. These findings suggest that the expression of IL-11Ra is an important factor for the invasion of human colorectal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…In women with endometrial cancer, IL11 levels are elevated in uterine lavage fluid and are positively associated with higher endometrial tumor grades (16). IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19). Studies have reported protumorigenic roles for IL11 in several epithelial cancers, including breast (20) and colorectal cancer (19) and one recent study highlighted a predominant role for IL11 rather than IL6 in mediating gastric cancer (21).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…In women with endometrial cancer, IL11 levels are elevated in uterine lavage fluid and are positively associated with higher endometrial tumor grades (16). IL11 protein (16) and mRNA (17), along with IL11Ra protein levels are progressively increased with increased endometrial tumor grade (16), which is in line with findings in other tumor types such as ovarian and colorectal (18,19). Studies have reported protumorigenic roles for IL11 in several epithelial cancers, including breast (20) and colorectal cancer (19) and one recent study highlighted a predominant role for IL11 rather than IL6 in mediating gastric cancer (21).…”
Section: Introductionsupporting
confidence: 74%
“…Recently, IL11 was implicated in experimental models of chronic inflammation and associated tumorigenesis, mediated, at least in part, by overactivation of STAT3 (38). In addition, high IL11 and IL11Ra expression are associated with tumor progression, cellular growth, and differentiation and poor prognosis in a number of cancers including colorectal (19), gastric (38), hepatocellular (39), and breast (20). IL11 is also highly expressed in metastatic lesions of hepatocellular carcinoma (40), and increases the metastatic potential of breast cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that IL11 is a novel hypoxia-inducible and VHL-regulated gene in human cancer cells. The expression of IL-11 and its receptor (IL-11Ra) has been extensively described in several human malignancies, including but not limited to prostate cancer and osteosarcoma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), suggesting its potential involvement in human tumorigenesis. However, the regulation of IL-11 expression is still poorly understood and its contribution, if any, to tumor progression is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the expression of IL-11 and the IL-11 receptor in colon cancer have been contradictory (38,39), but IL-11 has no direct effect on the growth of colon carcinoma cell lines in vitro (40). Moreover, whereas s.c. injections with recombinant IL-11 protects mice from thoracic radiation injury, the radiosensitivity of pulmonary breast cancer metastases is not affected (41).…”
Section: Discussionmentioning
confidence: 99%